“How Much Truth Can a Spirit Dare?” Nietzsche’s “Ethical” Truth Theory as an Epistemic Background for Philosophizing with Children - Marsal, Eva (ETHICS IN PROGRESS, 2011)
Philosophizing, according to E. Martens, can be seen as an elemental cultural technology, like arithmetic or writing, which both can and should be acquired in childhood. Martens is proposing here an understanding of philosophy that attributes value not only to the content canon, but also to the process itself, as Wittgenstein, for one, also did when he stated in the Tractatus Logico-Philosophicus, “Philosophy is not a doctrine, but an activity.” For Socrates, this activity consisted in “giving an account of ourselves, our knowledge, our way of life.” In Nietzsche’s view, the precondition for this kind of accounting is the personal capacity for self-distancing, which allows us to grasp our quite individual primal experiences of emotion, perception, sudden illuminations of insight, and so on, as general concepts and logical structures.